MODL-21. Multi-omics investigation of medulloblastoma resistant models reveals functional association between intracellular regulatory networks and drug susceptibility. (3rd June 2022) - Mariotto, Elena; Rampazzo, Elena; Bortolozzi, Roberta; Rruga, Fatlum; Manfreda, Lorenzo; Marchioro, Chiara; Bresolin, Silvia; Viola, Giampietro; Persano, Luca
Abstract: Medulloblastoma (MB) is the most common malignant brain tumor of childhood. Despite high-dose radio/chemotherapy treatment, 15-30% of patients still display a high risk of tumor recurrence. In this context, the characterization of innovative cellular models resembling therapy-induced drug resistance represents an unprecedented opportunity for selecting relevant therapies for chemotherapy-refractory patients. In order to unveil the molecular mechanisms sustaining chemotherapy resistance in MB, we setup in vitro models of MB drug resistance by exposing Patient-Derived MB (PD-MB) cells to a combination of the commonly used chemotherapeutics for pediatric MB treatment. Integration of multi-omics data, including transcriptional, proteomic and kinase activation profiling, disclosed that drug resistant PD-MB cells are characterized by a significant deregulation of several cancer-related pathways converging to metabolism of xenobiotics, adaptation of the biochemical processes sustaining energetic metabolic demand, cell proliferation and survival, protein homeostasis, RNA processing and modification, and immune response. Moreover, this intriguing regulatory network was functionally associated to the response of drug-resistant MB cells to a large library of compounds through a semi-automated High-Throughput drug Screening (HTS) workflow, suggesting the antimetabolite class of drugs as relevant therapeutics displaying high selectivity and efficacy against resistant MB models, together with a significant synergistic action when combined with standard chemotherapeutic agents. Collectively, our results suggest that drug-resistant MB cells are subjected to a peculiar adaptation of multiple intracellular processes during adaptation to chemotherapy, which protects them from the toxic environment but, at the same time, provides targetable vulnerabilities for therapeutic purposes.